An Objective Diagnosis Model with Integrated Metabolic and Immunity Parameters for Phlegm-Dampness Constitution. (4th February 2022) - Huang, Yanchun; Guo, Shanshan; Yang, Jun; Tang, Yangfan; Zhu, Xinghua; Ren, Sichong
Abstract : Background . According to Chinese constitutional theory, people can be divided into nine constitutions, which represent distinctive vulnerability to different diseases such as metabolic syndrome, atherosclerosis, and immunity-related disease, and so forth in modern medicine, phlegm-dampness constitution (PDC) is one of the nine constitutions, which is susceptible to metabolic syndrome (MS) and atherosclerosis that associate with lipid metabolism and immunity dysregulation closely. Objectives . In this study, we aimed to investigate the metabolic and immunity profiles of phlegm-damp constitution (PDC), including metabolites, lymphocytes distribution, and inflammatory cytokines. Methods . A total of 74 patients with PDC and 66 individuals with gentle constitution (GC) were enrolled in this study. We utilized biochemical methods to detect metabolic parameters, flow cytometry to survey T/B/NK/NKT lymphocyte subgroups distribution, and ELISA to assay inflammatory cytokines. Results . The subjects with PDC had higher GLU, AI TC, TG, and LDL-C and lower HDL-C levels. The immunity profile indicated that PDC subjects had higher percentage of WBCs, neutrophils, lymphocytes, B cells, and natural killer T cells compared with subjects with GC (P < 0.05 ). Serum levels of IL-10 decreased significantly in the subjects with phlegm-damp constitution, whereas IL-12 levels increased dramatically in the PDC group compared with the GC group (both P < 0.05 ). Additionally, logistic regression identified four independent variables (GLU, TG, LDL-C, and lymphocytes) that were highly correlated with PDC (P < 0.05 ). The area under the curve of the receiver operating characteristic curve was 0.878, which indicated the data were reliable to distinguish the subjects with PDC from the ones with GC. Conclusion . Phlegm-damp constitution was prone to hyperglycemia and hyperlipidemia syndrome, promoting the occurrence and progression of metabolic-related diseases. Interestingly, proinflammatory cells and cytokines were activated in the PDC group as well. Our findings could offer a profile of early screening indicators to identify high-risk patients of metabolic- and immunity-related diseases from Chinese constitution.